Knowledge, attitudes, and practices of community nutritionists and pharmacy professionals regarding nutrition and lifestyle counseling - A. Alsabbah, Amnah; Yamani, Israa Mohammed; Alzaidi, Thuraya Abdullah; Al Barakati, Hani Abdulelah; Alsharif , Waad Hamed; Allehyani, Fayhaa saleh; Alhothaly, Raghad Raddah; Gah, Sumayyah Abdullah Wan; Al-Harbi, Ghadeer Abdul Rahman; ALSUDANI, NORAH FAISAL Othman (Journal of Ecohumanism, 2024)
Community nutritionists and pharmacy professionals (CPPs) play a pivotal role in health promotion by providing nutrition and lifestyle counseling. Despite their accessibility and potential impact, gaps in knowledge, attitudes, and practices (KAP) regarding nutritional guidance remain understudied. This study aimed to assess the KAP of these professionals in counseling on dietary supplements, drug-food interactions, and dietary precautions, while identifying barriers and strategies for improvement. A cross-sectional study was conducted among 100 community nutritionists and pharmacy professionals, selected via stratified random sampling. Data were collected using a structured questionnaire, adapted from prior research, covering demographic details, KAP assessments, and barriers to counseling. Descriptive and comparative analyses were performed using SPSS version 26. Participants were predominantly female (60%), aged 25–34 years (55%), and held bachelor’s degrees (70%). Dietary recall (65%) and BMI calculation (55%) were the most common nutritional assessment methods. While 70% felt confident in general dietary guidelines, confidence dropped for therapeutic nutrition (40%) and pediatric nutrition (35%). Daily counseling was reported by 50% of participants, primarily for pregnant women (75%) and diabetic patients (85%). Key barriers included lack of time (65%) and insufficient knowledge (50%). Strategies proposed included continuing education (70%) and integrating nutrition into routine consultations (55%). The study highlights adequate baseline knowledge but identifies significant gaps in specialized areas like therapeutic and pediatric nutrition. Barriers such as time constraints and knowledge deficits underscore the need for enhanced training and systemic support. Integrating structured nutrition education into professional curricula and practice could empower CPPs to better address public health needs through effective counseling.